Apology Strategies in Situational Comedy: Ifid Analysis - Siti Tuti Alawiyah; Nico Harared (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Sometimes when someone who has made mistakes or says a statement which causes offence to others, she/he needs to maintain that kind of situation in response by apologies. The research aims at describing the strategies of apology in situational comedy. The data of this research were collected from dialogues that consist of apology in The Big Bang Theory. The data were analyzed qualitatively by examining the theory of apology strategy by Cohen and Olshtain (1986). Findings have shown that there are five strategies of apology utterances namely IFID, IFID + Explanation, IFID + Explanation + Requests, IFID + Responsibility + Requests and IFID + Explanation + IFID.